Prevalence and antifungal drug resistance of nosocomial Candida species isolated from two university hospitals in Egypt - Amira M El-Ganiny; Nehal Yossef; Hend Kamel (Mazandaran University of Medical Sciences, 2021)
Background and Purpose: There is a significant rise in morbidity and mortality of infections caused by Candida. Candida spp. infections are currently ranked fourth among nosocomial infections which are difficult to diagnose and refractory to therapy.Given the differences in susceptibility among various spp., identification of Candida spp. is an important step that leads to the selection of a suitable antifungal. Materials and Methods: A prevalence study was on 122 Candida isolates. The Candida spp. were identified using Chromogenic agar and polymerase chain reaction (PCR). The antifungal susceptibility (AFS) of Candida spp. to amphotericin B, fluconazole,voriconazole, and caspofungin was determined by the disc diffusion method. Results: In total, 122 Candida clinical isolates were investigated in this study. Candida albicans with 57.4% (70 isolates) had the highest prevalence rate, while 52 isolates (42.6%) were non-albicans Candida species (NAC). The NAC include Candida krusei (20.4%), Candida tropicalis (6.5%), Candida parapsilolsis (5.7%), Candida dubliniensis (4.9%), and Candida glabrata (4.9%). The AFS showed that the resistance rates of Candida spp. to fluconazole and voriconazole were 13.1% (16 isolates) and 9.8% (12 isolates), respectively. Moreover, only five isolates (4.1%) were resistant to caspofungin. Furthermore, there was no resistance against amphotericin B. The spp. that showed the highest resistance were C. glabrata and C. tropicalis, while the lowest resistance was observed in C. albicans and C. dubliniensis. Conclusion: In conclusion, rapid identification of clinical Candida isolates and standard AFS are essential procedures for controlling the rise of resistant NAC spp.in clinical settings. Usage of fluconazole should be restricted, especially in patients with recurrent Candida infections.